Ranking otwartych funduszy emerytalnych - Chybalski, Filip (Open Pension Funds Ranking, 2006)
The market of open pension funds in Poland has been existing since 1999 but the choices of pension fund made by Poles are not based on economical criteria. Because of that the need of assessing open pension funds in an understandable way is observed. The main aim of the article is the construction of open pension funds ranking based on a synthetic measure The variables creating the synthetic measure are the most important variables, which characterize the activity of open pension funds and its effects. There are the rate of return, modified standard semi-deviation, assets of open pension fund, charges for universal pension fund society, managing open pension fund and assets of universal pension fund society. The different meaning of these variables for the final rating of open pension funds must by pointed out. It is possible by assignment wages to the variables. Finally, we receive the ranking of open pension funds in which every fund has a note from the interval <0,1>. The best open pension fund receives the highest note.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 124-131